The Impact of Socioeconomic and Behavioral Factors on Health Indicators in OIC Countries - Susanto, Astiani; Irfany, Mohammad Iqbal; Camara, Bumi; Haq, Daffa Aqomal (AL-MUZARA'AH, 2025)
Health sector indicators are important basis of determining the overall state of a nation’s wealth and welfare. Apart from this broad and conventional perspective on the role of health, in many Islamic countries, health is also part of objective of ‘maqashid sharia’ that needs to be maintained to sustain life. Accordingly, countries invest substantial share of national resources to sustain critical health systems. Notwithstanding these commitments, health service delivery remains a major challenge in these countries, as indicated by the low average life expectancy and the high mortality rate caused by communicable diseases. This study aims to describe and analyze the factors influencing health outcomes, namely life expectancy and mortality rate, in Muslim countries using secondary data from 46 OIC countries from 2010-2018. Employing panel data estimation, the study finds evidence suggesting the important role of a nation’s wealth, health expenditure, educational achievement and the prevalence of smoking as important determinants of life expectancy in OIC countries. In particular, the results show that high incidence of communicable diseases in countries with lower than mean years of schooling and those with significantly wide prevalence of smoking habits may have contributed to high mortality in these countries.